Physical and photocatalytic properties of CeO2/ZnO/ZnAl2O4 ternary nanocomposite prepared by co-precipitation method - Wararat Somraksa (2020)
© 2020 Universidade Federal de Sao Carlos. All rights reserved. ZnAl2O4 spinel nanoparticles and CeO2/ZnO/ZnAl2O4 ternary nanocomposites were synthesized by a co-precipitation method. The structural, morphological, optical properties and chemical compositions of the products were analyzed respectively by X-ray diffraction (XRD), scanning electron microscopy (SEM), diffuse reflectance spectroscopy (DRS) and X-ray fluorescence (XRF) spectroscopy. The optical band gap of ZnAl2O4 spinel nanoparticles was 3.220 eV. When 1.0 mmol Ce(NO3)3•6H2O was added to the synthesis reaction, the optical band gap of the obtained ternary nanocomposite was 3.170 eV. The influence of phase composition, optical band gap, oxygen vacancy and specific surface area on photocatalytic activity over CeO2/ZnO/ZnAl2O4 ternary nanocomposites was investigated. The CeO2/ZnO/ZnAl2O4 nanocomposite prepared with 1.0 mmol Ce(NO3)3•6H2O showed the lowest recombination rate of photoexcited electron-hole pairs, the narrowest optical band gap (3.170 eV) and the highest oxygen vacancy concentration or highest Urbatch energy (0.299 eV). These parameters produced the best photocatalytic activity toward methylene blue (MB) under UV irradiation. The CeO2/ZnO/ZnAl2O4 ternary nanocomposites exhibited better photocatalytic performance than pure ZnAl2O4 spinel nanoparticles and 100% degradation of aqueous MB solution was achieved within 60 min when using the CeO2/ZnO/ZnAl2O4 ternary nanocomposite photocatalyst synthesized with 1.0 mmol Ce(NO3)3•6H2O.